2012
DOI: 10.1017/s0003055412000226
|View full text |Cite
|
Sign up to set email alerts
|

The Civic Origins of Progressive Policy Change: Combating Violence against Women in Global Perspective, 1975–2005

Abstract: O ver the past four decades, violence against women (VAW) has come to be seen as a violation of human rights and an important concern for social policy. Yet government action remains uneven. Some countries have adopted comprehensive policies to combat VAW, whereas others have been slow to address the problem. Using an original dataset of social movements and VAW policies in 70 countries over four decades, we show that feminist mobilization in civil society-not intra-legislative political phenomena such as left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
297
2
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(318 citation statements)
references
References 112 publications
9
297
2
10
Order By: Relevance
“…Putting these two forms of contextual analyses together is where the structures of social, cultural and political contexts meet the individual behaviors (Htun & Weldon, 2012). Even for socalled "intimate" and private behaviors within relationships between partners, such as common knowledge that secrets can and should be kept within relationships, the behaviors cannot maintain functionally without a wider societal acceptance and modeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putting these two forms of contextual analyses together is where the structures of social, cultural and political contexts meet the individual behaviors (Htun & Weldon, 2012). Even for socalled "intimate" and private behaviors within relationships between partners, such as common knowledge that secrets can and should be kept within relationships, the behaviors cannot maintain functionally without a wider societal acceptance and modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we need to include these in our behavioral or contextual analysis of the behaviors of individuals, as pre-existing contexts (societal structures) utilized by the men-or pre-existing contingency structures if you will. This is reflected in a recent review by Htun and Weldon (2012) of global policy changes to reduce violence against women. They wrote:…”
Section: How Societal Contingency Structures Appear In Individual Behmentioning
confidence: 99%
“…Legal strategies have been utilized by feminist organizations worldwide to address the problem of gender-based violence (Friedman 2009). Research has shown that such advocacy is crucial to expanding women's rights (Htun and Weldon 2012). Yet the foregoing discussion also illustrates the fragility of these gains in contexts characterized by a high concentration of political power.…”
Section: The Backlash Against the Lawmentioning
confidence: 98%
“…In countries where new legislation to advance women's rights did pass, cross-national research has shown that the decisive factor was not the intervention of multilateral institutions but rather the work of vibrant grassroots feminist movements (Htun and Weldon 2012). Such movements are critical, not only because they place pressure on states, but also because they can 'translate' global human rights norms in culturally relevant ways, thereby countering accusations of 'imperialistic intervention,' and building local support for legal change (Figueroa and Barbeyto 2014;Merry 2006 (Sarmiento et al 2014).…”
Section: Gender-based Violence Law and Global Governancementioning
confidence: 99%
“…This is a profound crisis in our way to do politics. This statement about feminists' spaces after the coup reveals the challenges the new political context in Honduras imposed because feminist organisations have generally proven to be fundamental to achieve equal rights and integrate women's rights into policy-making (Htun & Weldon, 2012). Their resources were constrained because to both react to the political crisis and continue with feminist politics proved demanding.…”
Section: Uniting Spatial Imaginaries In Protests: the Aftermath Of Thmentioning
confidence: 99%